2015
DOI: 10.1038/srep10107
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Different Types of Surfactants on Zebrafish Embryos and Larvae

Abstract: Currently, surfactants are widely distributed in the environment. As organic pollutants, their toxicities have drawn extensive attention. In this study, the effects of anionic [sodium dodecyl sulphate (SDS) ], cationic [dodecyl dimethyl benzyl ammonium chloride (1227)] and non-ionic [fatty alcohol polyoxyethylene ether (AEO) ] surfactants on zebrafish larval behaviour were evaluated. Five behavioural parameters were recorded using a larval rest/wake assay, including rest total, number of rest bouts, rest bouts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 47 publications
4
44
0
Order By: Relevance
“…Therefore, we speculated that they should also be similar in both male and female brains. Available evidence showed that many genes in the list of 108 sex-based genes we obtained in this study involves in neural circuit or brain development, e.g., egr2b (early growth response 2b, also known as KROX20) [24], mych (myelocytomatosis oncogene homolog) [25], and hrh3 (histamine receptor H3) [26]. In addition, we found that some genes play a similar role in the brain of zebrafish and humans.…”
Section: Discussionsupporting
confidence: 61%
“…Therefore, we speculated that they should also be similar in both male and female brains. Available evidence showed that many genes in the list of 108 sex-based genes we obtained in this study involves in neural circuit or brain development, e.g., egr2b (early growth response 2b, also known as KROX20) [24], mych (myelocytomatosis oncogene homolog) [25], and hrh3 (histamine receptor H3) [26]. In addition, we found that some genes play a similar role in the brain of zebrafish and humans.…”
Section: Discussionsupporting
confidence: 61%
“…Digoxigenin-labeled probes (for cmlc2 , amhc and vmhc ) and whole-mount in situ hybridization were performed as previously described (Wang et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…One of the synthetic anionic surfactants, sodium dodecyl sulfate (SDS), or sodium lauryl sulfate (SLS), a product that consists of approximately 70% sodium dodecyl sulfate and 30% sodium tetradecyl sulfate, with the formula of CH3(CH2) 11 OSO 3 Na, has been used in many cleaning and hygiene products such as liquid soaps, shampoos, bubble baths, shower gels, and nearly all toothpastes. SDS is also used in pharmaceutical and food products, as well as in industiral and laboratory applications, i.e., SDS can form complexes with protein through hydrophobic interactions and thus be used in polyacrylamide gel electrophoresis to determine the molecular weight of proteins [1,2]. The concentration of SDS found in consumer products varies by product and manufacturer but typically ranges from 0.01 to 50% in cosmetic products and 1 to 30% in cleaning products [3].…”
Section: Introductionmentioning
confidence: 99%